Analisis Reaksi Investor Terhadap Pengumuman Right Issue di Pasar Modal Indonesia. Analysis of Investors' Reaction To Right Issue Announcements in Indonesia's Capita - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
The purpose of this study is to investigate the investors' reaction to rights issue announcements in Indonesia's capital market. Investors' reaction is proxied by abnormal return surrounding announcement day. Significant abnormal return indicates that there is information contents on rights issue announcements, and this study is to investigate whether the amount of capital raised (relative to existing capital), firm size, stock return variance, offer price, and decrease in leverage are the determinants in such investors' reaction.The samples are the rights issues by firms listed in Jakarta Stock Exchange during the period 1993-1997. The event study with 21 event window (from day -10 to day +10) is used to investigate the investors' reaction. Abnormal return was calculated by market-adjusted model. Linier regression between cumulative abnormal return for several days (determined based on abnormal return significancy) as a dependent variable and independent variables (amount of capital raised, firm size, stock return variance, offer price, and decrease in leverage) is used to investigate the determinants in investors' reaction.Investors perceive the rights issue announcements positively, since there is a significant positive abnormal return surrounding announcements day. Abnormal return on day -2 and -1 was 0,7922% and 0,7953% respectively (significant at 95% and 90% level of confidence) and abnormal return day 0 was 0,5835% (insignificant).The regression results indicate that issuer firms stock abnormal return (as proxy for investors' reaction) was positively influenced by the amount of capital raised (relative to existing capital) and the magnitude of offer price, and negatively was influenced by the decrease on leverage ratio of issuer firms.